2021
DOI: 10.1055/s-0041-1739199
|View full text |Cite
|
Sign up to set email alerts
|

Crohn's Disease Increases In-Hospital Lengths of Stay, Medical Complications, and Costs of Care following Primary Total Knee Arthroplasty

Abstract: The literature has shown an increase in prevalence of Crohn's disease (CD) within the United States alongside a concomitant rise in primary total knee arthroplasty (TKA) procedures. As such, with these parallel increases, orthopaedic surgeons will invariably encounter CD patients requiring TKA. Limited studies exist evaluating the impact of this disease on patients undergoing the procedure; therefore, this study endeavors to determine whether CD patients undergoing primary TKA have higher rates of (1) in-hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The included studies were all conducted in the USA. Six studies collected data from nationwide administrative databases, 5,18,19,[21][22][23] and two from a single-centre hospital database. 20,24 Five studies reported mixed cohorts of patients suffering from IBD 5,[19][20][21]24 and three included patients with CD only.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies were all conducted in the USA. Six studies collected data from nationwide administrative databases, 5,18,19,[21][22][23] and two from a single-centre hospital database. 20,24 Five studies reported mixed cohorts of patients suffering from IBD 5,[19][20][21]24 and three included patients with CD only.…”
Section: Resultsmentioning
confidence: 99%
“…20,24 Five studies reported mixed cohorts of patients suffering from IBD 5,[19][20][21]24 and three included patients with CD only. 18,22,23 One study investigated hip, knee, and shoulder arthroplasty, 21 two investigated hip and knee arthroplasty, 5,24 two investigated total knee arthroplasty only, 22,23 and three investigated total hip arthroplasty only. [18][19][20] The International Classification of Diseases, Ninth/Tenth Revision (ICD-9/10) diagnosis codes were used to diagnose IBD in seven studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations